Facial Location and Operating Room Environment are the Risk Factors for Incomplete Excision of Melanocytic Nevi - Zgraj, Oskar; Taczanowska-Niemczuk, Anna; Gorecki, Wojciech (European Journal of Pediatric Surgery, 2019)
Introduction The management of melanocytic nevi involves many various practitioners with a high number of patients. Data on failure to achieve goals of treatment are scarce. We aimed to determine percentage of incompletely excised nevi and the risk factors responsible.Materials and Methods In this retrospective cohort study, histology reports of all melanocytic nevi excised within our department between January 2014 and June 2015 were considered. Those aimed for stage excision and those with inconclusive histology reports were excluded. Patients' age, sex, anatomical location of the lesion, its size, as well as source of specimen (general surgical outpatients, surgical oncology outpatients, and operating room), and performing surgeon (trainee vs. consultant) were recorded. Chi-square test was used for statistical analysis with a p-value of < 0.05 considered significant.Results A total of 739 nevi in 541 patients were analyzed. Positive margins were found in 80 (11%) of all specimens. There was significantly increased rate of incomplete excision of nevi from the facial area (42%; p < 0.001) versus other areas and, surprisingly, those excised in the operating room under general anesthesia (19%; p = 0.009). Nevi excised at our surgical oncology outpatients had the lowest rate (8%, p = 0.013) of incomplete excisions. There were no statistically significant differences in other variables.Conclusion We identified facial location and operating room environment as risk factors for incomplete excision of melanocytic nevi. We suggest that human factors play a key role in achieving a good quality of service.
Keywords: nevi; excision; margins; pediatric; children